Thermal and electrochemical studies of Fe(III) organophilic montmorillonite - Franzin, Bruno Trevizan [UNESP]; Lupi, Caroline Polini [UNESP]; Martins, Lucas Alves [UNESP]; Guizellini, Filipe Corrêa; dos Santos, Cecília Cristina Marques [UNESP]; Pastre, Iêda Aparecida [UNESP]; Fertonani, Fernando Luis [UNESP] (Springer Nature, 2018)
This study aimed at investigating the thermal and electrochemical behavior of montmorillonite clay-8-hydroxyquinoline (8-HQ) film in the absence and presence of aqueous Fe(III) ions. The solid film characterization by means of UV spectroscopy, thermal (TG/DTG and TG–DTA, simultaneous) studies, SEM and optical images, and XRD suggested the formation of the ternary complex type: {Pt/[>Si–O]n[Fe(III)(OH2)3(8-HQ)k]}3−n−k, with thermal stability up to 300 °C. The electrochemical study was carried out on a platinum electrode modified by mechanical deposition of a thin solid film of the binary composite (SWy-1:8-HQ) from an aqueous suspension. The mechanical stability of the film was followed by performing 80 cyclic voltammograms. The electrochemical behavior of the modified electrode was investigated using cyclic voltammetry (CV) at different ferric ions concentration (CFe(III)), followed by a study of the effect of the scan rate (v) with a fixed CFe(III) ions. In the CVs, two independent pairs of current peaks, A/D and C/B, were observed. For Fe(III) ions in solution, log ip versus log v relationship shows a process controlled first by adsorption (pair of peaks A/D) and then by diffusion control (pair of peaks C/B). The current function ip/v1/2 versus v and ip a/ip c versus v allowed a suggestion of two homogeneous coupled chemical reactions associated with CE and EC mechanisms, respectively, both with fast reversible chemical reactions. The first investigation of a modified electrode showed good sensitivity (S = 25.1 μA/μmol L−1) to low concentrations of ferric ions and detection limit [LOD = (2.4 ± 0.01) μmol L−1] and high sensitivity to traces of O2, showing that this system has great analytical potentials.
Keywords: Determination of Fe(III) ions; Electrochemistry; Organic montmorillonite; Pt-modified electrode; TG–DTA; XRD